Modulatory effects in circadian-related diseases via the reciprocity of tea polyphenols and intestinal microbiota - Ruonan Yan; Chi-Tang Ho; Xin Zhang (Food Science and Human Wellness)
Tea is a widespread functional plant resource. Phytochemicals such as tea polyphenols (TP) can interact with the intestinal flora and participate in regulating the expression and rhythm of biological clock genes. Circadian rhythm controls a variety of behaviors and physiological processes, and circadian misalignment has been found to be closely related to multiple metabolic diseases. Interestingly, the gut microbiota also has diurnal fluctuations, which can be affected by diet composition and feeding rhythm, and play a role in maintaining the host’s circadian rhythm. The two-way relationship between the host’s circadian rhythm and intestinal microbiota confirms the possibility that prebiotics or probiotic can be used to adjust the intestinal environment and microbiome composition to improve the host health. This article reviews the relationship between the host’s circadian rhythm and microbiota and its influence on metabolic diseases. The beneficial effects of the interaction between TP and gut microbiota on diseases related to rhythm disorders are emphasized to improve the theories of disease prevention and treatment.